O-06 Bereavement pandemic: developing a multi-intervention model for wellbeing in care home communities. (19th November 2022) - Harkness, Charlotte; Basson, Sharon
Abstract : The pandemic has had a devastating impact on people in care home communities. At the peak in 2020, deaths in care homes rose by 159% (Healthwatch Suffolk, 2021). The Healthwatch Suffolk report indicates several areas for improvement in the support of bereaved people: 58% of family members related to a person who died in a care home were not present at death and of all people who were bereaved during this period, those bereaved of someone who died in a care home were least likely to be offered bereavement support (14% compared with 63% of those bereaved of someone who died in hospice). As well as people in care homes being less likely to have access to bereavement support, we also know that COVID deaths were often traumatic, potentially leading to a need for greater bereavement support (Spurio, 2021. Psychiatr Danub. 33, S.9:102). This project addresses this inequity, embedding care home support into the hospice's open access bereavement services, in line with the ICS's commitment to ensure that 'people bereaved [should] have the support they need to cope with trauma and loss' (Healthwatch Suffolk, 2021). A multi-disciplinary model has been developed involving psychological services, chaplaincy services, community connectors and hospice neighbours. A targeted range of interventions is being delivered within care homes, focussing on: People that are the significant others of a person who died. Bereaved residents including those whose peer has died. Residents approaching the end of their lives and their significant others. Care home staff. The initial pilot roll-out covers 3 care homes. Bespoke assessment tools have been developed in order to measure the impact of each of the interventions and the project as a whole. This paper outlines project design, key parameters and pilot data and will show how the reflexivity built into the design enables a continual process of service development.